ZmRAD17 Is Required for Accurate Double-Strand Break Repair During Maize Male Meiosis - Zhang, Ting; Jing, Ju-Li; Liu, Lei; He, Yan (Frontiers in Plant Science, 2021)
RAD17, a replication factor C (RFC)-like DNA damage sensor protein, is involved in DNA checkpoint control and required for both meiosis and mitosis in yeast and mammals. In plant, the meiotic function of RAD17 was only reported in rice so far. Here, we identified and characterized the RAD17 homolog in maize. The Zmrad17 mutants exhibited normal vegetative growth but male was partially sterile. In Zmrad17 pollen mother cells, non-homologous chromosome entanglement and chromosome fragmentation were frequently observed. Immunofluorescence analysis manifested that DSB formation occurred as normal and the loading pattern of RAD51 signals was similar to wild-type at the early stage of prophase I in the mutants. The localization of the axial element ASY1 was normal, while the assembly of the central element ZYP1 was severely disrupted in Zmrad17 meiocytes. Surprisingly, no obvious defect in female sterility was observed in Zmrad17 mutants. Taken together, our results suggest that ZmRAD17 is involved in DSB repair likely by promoting synaptonemal complex assembly in maize male meiosis. These phenomena highlight a high extent of divergence from its counterpart in rice, indicating that the RAD17 dysfunction can result in a drastic dissimilarity in meiotic outcome in different plant species.